PENGARUH PENGGUNAAN AMPAS SAGU SEBAGAI PUPUK KOMPOS TERHADAP PERTUMBUHAN TANAMAN KACANG HIJAU - Ida Andayani; Karunia Gea; Leonardus Historis Manao (Universitas Nias Raya, 2024)
Low productivity of green bean plants (Vigna radiata L.). This research aims to determine the effect of using sago dregs as compost on the growth of green bean plants (Vigna radiata L.). This type of research is descriptive type quantitative research with a pure experimental method (True experiment). The population in this study were all green bean plants that had been seeded, while the samples were the green bean plants themselves, consisting of 30 polybags, six treatments with 5 repetitions. The treatments applied are: P0=0 grams, P1= 50 grams, P2=100 grams, P3=150 grams, P4=200 grams, P5=250 grams. The data in this study were analyzed using normality tests, homogeneity tests and hypothesis tests using the SPSS version 15 application. Based on the results of the research, it shows that there is an influence of using Sago Dregs as Compost Fertilizer on the Growth of Green Bean Plants (Vigna radiata L.) in each treatment and replication, namely starting from the first treatment to the fifth treatment and good growth of green bean plants was at a dose of 250 grams (5th Treatment). The suggestion from researchers is that people should be able to use Sago Dregs as a type of natural fertilizer for green bean plants because this fertilizer, apart from fertilizing the soil, also increases more optimal growth of green bean plants.